Eco-friendly (green) synthesis of magnetically active gold nanoclusters. Issue 1 (31st December 2017) - Kadasala, Naveen Reddy; Lin, Lu; Gilpin, Christopher; Wei, Alexander
Abstract: Au–Fex Oy composite nanoparticles (NPs) are of great technological interest due to their combined optical and magnetic properties. However, typical syntheses are neither simple nor ecologically friendly, creating a challenging situation for process scale-up. Here we describe conditions for preparing Au–Fex Oy NPs in aqueous solutions and at ambient temperatures, without resorting to solvents or amphiphilic surfactants with poor sustainability profiles. These magnetic gold nanoclusters (MGNCs) are prepared in practical yields with average sizes slightly below 100 nm, and surface plasmon resonances that extend to near-infrared wavelengths, and sufficient magnetic moment (up to 6 emu g –1 ) to permit collection within minutes by handheld magnets. The MGNCs also produce significant photoluminescence when excited at 488 nm. Energy dispersive X-ray (EDX) analysis indicates a relatively even distribution of Fe within the MGNCs, as opposed to a central magnetic core. Abstract :